Menggagas Pendirian Bank Digital di Indonesia: Sebuah Telaah Yuridis - Danang Kurniawan; Wardah Yuspin (Universitas Islam Balitar, Blitar, 2023)
In the industrial era 4.0 as it is today, the ease and speed of getting things are highly sought after, including the ease and speed of getting financial services. The convenience of banking services is an advantage for consumers in choosing the services provided at the bank. This is what banks do to form services from conventional banks to open digital services. However, from a juridical aspect, in Indonesia there is no specific regulation governing digital banks. As a country that adheres to the civil law system, it has become a real consequence that all applicable laws must be codified and regulated in accordance with applicable laws. Problems arise when digital banks operate but there is no legal basis that specifically regulates dealing with it. Through normative juridical methods, research results showed that there are no specific rules governing digital banks in the form of laws in Indonesia, so a special rule is needed regarding digital banks because there are significant differences from conventional banks.